EVENT MARKETING URBAN GIGS SEBAGAI BENTUK KOMUNIKASI PEMASARAN DALAM MEMBANGUN BRAND IMAGE PRODUK GG MILD DI PEKANBARU - Tri Suci Nadilla Fitri; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Event marketing is a type of promotion where companies or brands connect to events or where themed activities are built for the purpose of creating consumer experiences and also for promoting products or services. PT. Surya Madistrindo, Tbk one of the tobacco companies that use event marketing media as a form of marketing strategy in promoting GG Mild product to build brand image, that is by organizing Urban GiGs event. With the event marketing helps increase sales and the process of building a brand image of GG Mild product is the style of new generation where GG Mild products are expected to be consumed by young people as next generation smokers. This study aims to determine the segmentation, targeting, and positioning (STP) marketing communication PT. Surya Madistrindo, Tbk.This research uses descriptive qualitative method with observation data collection techniques, interviews, and documentation. The data obtained are then processed to be reduced, presented until a general conclusion is produced. Informants in this study amounted to 5 based on purposive methods that researchers use. As for the examination of data validity, the researcher uses the technique of extension of participation and trigger.The results of this study show that segmentation, targeting, positioning (STP) marketing PT. Surya Madistrindo, Tbk through Urban GiGs marketing event in building the brand image of GG Mild product in Pekanbaru. Segmentation is a man who likes art, fashion, travel, and music. Targeting of Urban GiGs event event there are millenial young people aged 18-25 years. Positioning is GG Mild product consumed by young generation next generation smokers. Postioning of Urban GiGs event to touch consumers, make consumers aware, and finally try to become a smoker GG Mild. Marketing communications activities conducted Urban GiGs marketing event in building the brand image of GG Mild product is as a strategy of promotion, building brand image and embedding image of GG Mild product to consumers. Some of the strategies the company does in the form of marketing communications him in Urban GiGs personal selling events, merchindase, games, and MC.Keywords: Event marketing, marketing communications, brand image